2006
DOI: 10.1016/j.ejvs.2005.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Local Anaesthetic Flush Reduces Postoperative Pain and Haematoma Formation After Great Saphenous Vein Stripping—A Randomised Controlled Trial

Abstract: Flushing of the GSV tunnel with bupivacaine plus adrenaline significantly reduces postoperative pain and haematoma formation in patients undergoing GSV stripping for varicose veins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 6 publications
0
26
1
1
Order By: Relevance
“…Our findings are consistent with data obtained in the surgical setting, where less surgical site bleeding has been reported with epinephrine-containing local anesthetic solutions. [1][2][3][4][5][6] We found that epinephrine-containing solutions did not result in more painful skin infiltration. Because epinephrine is unstable, premixed local anesthetic solutions with epinephrine are acidified to a pH of 4.15 in order to promote stability and solubility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are consistent with data obtained in the surgical setting, where less surgical site bleeding has been reported with epinephrine-containing local anesthetic solutions. [1][2][3][4][5][6] We found that epinephrine-containing solutions did not result in more painful skin infiltration. Because epinephrine is unstable, premixed local anesthetic solutions with epinephrine are acidified to a pH of 4.15 in order to promote stability and solubility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in surgical settings used similar subjective assessments to study the effect of epinephrine-containing local anesthetic solutions on perioperative bleeding from surgical wound sites. [1][2][3][4][5][6] In conclusion, local infiltration of epinephrine-containing lidocaine before labor epidural catheter insertion results in less superficial bleeding compared to plain lidocaine solutions. The addition of bicarbonate to lidocaine results in a modest reduction in pain on local anesthetic infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stripping of the long saphenous vein from groin to the kneec an sometimes be incomplete. 1 If al ong, strong ligature is used to attach thevein to thestripper it canbecontrolled at bothwounds after passing thes tripper.T ie the ligature onto al engtho fr ibbon gauze and pull this downt hrought he saphenous tunnel to exit at the kneewound. This gauze frequently brings thesaphenousvein remnantw ith it (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In einer vergleichenden Serie von ausgedehnten Wundexzisionen bei brandverletzten Kindern konnte kein Vorteil der Anwendung von topischer und subkutaner Adrenalingabe im Hinblick auf den Blutverlust nachgewiesen werden [2]. In einer jüngst publizierten randomisierten Doppelblindstudie (n=100) wiederum konnte ein positiver Effekt der lokalen Applikation eines Gemischs aus Bupivacain und Adrenalin im Hinblick auf Hämatombil-dung nach Varizenstripping nachgewiesen werden [22]. [9].…”
Section: > Die Lokale Applikation Vasoaktiver Substanzen Birgt Das Riunclassified